2009
DOI: 10.2108/zsj.26.704
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Estrogen Receptor β in the Induction of Polyovular Follicles in Mouse Ovaries Exposed Neonatally to Diethylstilbestrol

Abstract: Natural and synthetic estrogens, Including diethylstilbestrol (DES), given during the critical period of newborn life Induce abnormalities in ovaries of mice. Induction of polyovular follicles (PFs) containing two or more oocytes in a follicle is one example. In this study, the involvement of estrogen receptor subtypes ERalpha and ERbeta in induction of PFs by neonatal treatment with DES was analyzed by using ERalpha knockout (alphaERKO) and ERbeta knockout (betaERKO) mice. Ovaries of mice injected with 3 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…Interestingly, further studies on ESR deficient mice (aERKO and bERKO) have shown that DES (3 mg) induces ovarian abnormalities through different ESRs. Specifically, DES inhibits follicle formation and development through ESR1 (Kim et al 2009b), whereas it induces polyovular follicles through ESR2 (Kirigaya et al 2009). In mice, in utero exposure to DES (100 mg/kg) was shown to change ovarian morphology and alter ex vivo ovarian steroidogenesis in the offspring of the dosed dams (Haney et al 1984).…”
Section: Chemicals That Alter Hormone Receptor Binding and Actionmentioning
confidence: 99%
“…Interestingly, further studies on ESR deficient mice (aERKO and bERKO) have shown that DES (3 mg) induces ovarian abnormalities through different ESRs. Specifically, DES inhibits follicle formation and development through ESR1 (Kim et al 2009b), whereas it induces polyovular follicles through ESR2 (Kirigaya et al 2009). In mice, in utero exposure to DES (100 mg/kg) was shown to change ovarian morphology and alter ex vivo ovarian steroidogenesis in the offspring of the dosed dams (Haney et al 1984).…”
Section: Chemicals That Alter Hormone Receptor Binding and Actionmentioning
confidence: 99%
“…MOFs were also observed in ovaries that were treated in vitro at PND 1-5, following their transplantation to untreated mice, suggesting a direct effect of DES in the ovary [122]. Recent studies showed that neonatal exposure to 3 μg/kg DES induced MOFs, a process mediated by ESR2 and not ESR1 [97]. DES exposure was shown to reduce oocyte apoptosis (potentially suppressing oocyte nest breakdown) via ESR2 signaling mechanisms.…”
Section: Des In Vivo Studiesmentioning
confidence: 99%
“…These facts indicate that PF induction can be accompanied with changes in expression of those genes. Ηowever, no significant changes in the expression of Gdf9 and Bmp15 are found in the ovary of mice neonatally exposed to DES at 5, 20 and 30 days, but only Inha is increased (4,9). Since DES can bind and transactivate both ERα and ERβ (10,6), it is possible that changes in gene expression include all of the genes downstream of ERα and ERβ.…”
mentioning
confidence: 96%
“…Surprisingly, neonatal exposure to 4,4',4''-(4-propyl-[1H]-pyrazole-1,3,5-triyl) triphenol (PPT), a specific ERα agonist, also induces PFs in the mouse ovary at 30 days, although not having significant estrogenic activity on mouse ERβ in in vitro transactivation assay (6). These results suggest that both ERα and ERβ are involved in PF induction, however, ERβ is essential for PF induction because a lack of ERβ results in no PF induction in the ovary even after neonatal exposure to DES (4).…”
mentioning
confidence: 97%
See 1 more Smart Citation